Factors Influencing Investment Decisions Among University Students: The Roles of Financial Literacy, Lifestyle, Income, and Financial Planning - Siti Halimah Rambe; Noni Ardian; Hernawaty Hernawaty (Transpublika Publisher, 2025)
The rapid proliferation of financial technology and the effortless accessibility of digital investment platforms have significantly reshaped the investment landscape, allowing younger generations to begin investing with minimal capital while acquiring financial knowledge through diverse applications and virtual learning resources. Investment decision-making has become increasingly important among youth, who possess the temporal advantage to benefit from the compounding effect of returns, yet must simultaneously anticipate future challenges such as inflation, post-retirement uncertainty, and rising living costs. These circumstances highlight the necessity of building an investment portfolio early to achieve financial resilience and independence. This study aims to examine the influence of financial literacy, lifestyle, income level, and financial planning on students’ investment decisions. The research encompassed active part-time Fintech students in the Management Study Program (Friday–Saturday class), Faculty of Social Sciences, Universitas Pembangunan Panca Budi Medan, cohorts 2022–2023. Through the Slovin formula, 71 individuals were designated as the sample. A quantitative survey design was utilized, with questionnaire data processed via SPSS. Findings indicate that financial literacy exerts a salubrious and statistically weighty partial influence on investment decisions. Lifestyle also demonstrates a positively potent and preponderant effect. In contrast, income and financial planning show no substantive partial impact. Nonetheless, when assessed simultaneously, all four variables collectively manifest significant influence, reflected in F = 43.852, p < 0.001, R² = 0.727.